MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN MULTIPLAYCARDS - Ashar; Nurcahyani; Sri Novita Rahma; Rahmawati (Yayasan Nusantara Hasana Berdikari, 2023)
The lack of variation in the use of learning media and learning models used by teachers in learning mathematics causes low student mathematics learning outcomes. This study aims to improve mathematics lessons material arithmetic operations class V SD. This research is an improvement research that uses a classroom action research model which is a form of systematic reflective study by actors of action taken to improve their rational abilities and actions in carrying out tasks, deepen understanding of the actions they take, and improve learning conditions. Classroom action research is reflective, meaning that in the research process, the teacher is also a researcher who thinks about what and why an action occurs in the classroom, from that thought, the teacher then seeks a solution through certain actions. Classroom action research is research conducted with the aim of improving the quality of classroom practice, which is closely related to students and the teaching and learning process in class. The main objective of PTK is to solve real problems that occur in the classroom and increase the real activities of teachers in their professional development. This research involves repeated activities, namely: (1) planning, (2) implementation/action, observation/evaluation, (3) reflection, and (4) re-planning. Actions in this research will be carried out on an ongoing basis based on the formulated classroom action research criteria.